Mesh Material Feasibility Tests for Maximum Water Collection by using White PE Plastic Sheet, Black Polyoleﬁn Mesh and HDPE Green Mesh - Nur Hidayah Mohd Isa (2018)
Atmospheric water harvesting is an adaptation of natural processes of water cycles which involve condensation and precipitation process. The purposes of this study are to investigate the efficiency of mesh material test for maximum water collection and to determine the relationships of meteorological effects on the amount of water collected. ln order to investigate the efficiency of mesh material tests, it should possess the hydrophilicity and hydrophobicity on the surfaces to promote atmospheric water deposition. There are several types of material test were used in this study which is white PE plastic sheet, black Polyoleﬁn meshes, and HDPE green mesh. On the other hand, the primary data collection on volume of water collected was obtained from daily monitoring and secondary atmospheric data were also collected from Malaysian Meteorological Department website for 60 days and statistical analysis were carried out to compare the feasibility of material tests for maximum water collection. To relate the primary data and secondary data, multiple linear regression analysis were used in this study as well as to prove that meteorological effects and material properties of mesh can affect the volume of water collected. Basically, this study aimed to ﬁnd an alternative way to reduce water scarcity issues in highland area where the sources of surface water and sources of groundwater are almost none. As a result, the volume of water collected by mesh material tests does relate to the meteorological effects especially on rainfall amount as an option to open a new view on utilizing new source of water.